Design Strategies for Mobile Click-and-Load Waiting Scenarios - Yang Yin; Yingpin Chen; Chenan Wang; Yuching Chiang; Pinhao Wang; Haoran Wei; Haibo Lei; Chunlei Chai; Hao Fan (Applied Sciences, 2025)
The optimization of design strategies in loading and waiting scenarios is of great significance for enhancing user experience. This study focuses on the click-to-load waiting scenario in mobile device interfaces and systematically analyzes the user experience performance of three design strategies—the interface type, loading indicator, and layout—across different page transition types (including the tab page, content page, and half-screen overlay). Based on questionnaire responses and experimental data (N = 90) collected from participants aged 20–29, we assessed subjective user perceptions across five validated metrics: time perception, loading speed, satisfaction, emotional valence, and arousal level. The results revealed significant differences among strategies in terms of loading speed perception, time awareness, and emotional responses. Notably, progressive loading strategies proved particularly effective in enhancing user satisfaction and alleviating temporal cognitive load. This study summarizes the characteristics of strategy applicability and proposes general optimization recommendations, offering both theoretical insights and practical guidance for designing loading feedback in mobile device interfaces.